2002
DOI: 10.1046/j.1445-2197.2002.02287.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal position for a cervical collar incision: A prospective study

Abstract: Migration of a proposed cervical collar incision does occur. An inappropriately placed incision may lead to excessive scarring if it is too low, or unusual prominence if it is too high. We believe a good position for marking such an incision is 1 fingerbreadth above the sternal notch with the patient in a neutral, upright position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
9
1
Order By: Relevance
“…Harmonic scalpel has been approved by published studies to have better haemostatic effect in comparison to coventional technique 26,27 , our results does not report any cases of intraoperative or postoperative bleeding who need blood transfusion or reoperation in both groups. No mortality was reported in our study while published data reported negligible mortality due to thyroidectomy 28 .…”
Section: Discussioncontrasting
confidence: 51%
“…Harmonic scalpel has been approved by published studies to have better haemostatic effect in comparison to coventional technique 26,27 , our results does not report any cases of intraoperative or postoperative bleeding who need blood transfusion or reoperation in both groups. No mortality was reported in our study while published data reported negligible mortality due to thyroidectomy 28 .…”
Section: Discussioncontrasting
confidence: 51%
“…Perhaps using an adjustable or inflatable bag might have improved the situation. [14][15][16] However, the most direct and proper way of measuring neck extension during thyroidectomy would be to obtain an intraoperative fluoroscopic image. 8 In addition to pain, our study also evaluated other secondary outcome parameters, including operating time, blood loss, number of parathyroid glands seen and autotransplanted, rate of RLN injury, and postoperative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical team consists of the surgeon and three assistants, one of whom must hold the camera. A 20–35 mm skin incision is performed "high" between the cricoid and jugular notch, in the middle line on account of its upper migration when the patient is placed in the supine position [25]. …”
Section: Methodsmentioning
confidence: 99%